THE STUDY OF ACCURACY OF AN OPERATOR’S PERCEPTION OF GEOMETRICAL OBJECT SIZES AND SHAPES IN THE VIRTUAL ENVIRONMENTS - Tanryverdiev, Ilya; Petukhov, Igor; Steshina, Luydmila; Steshin, Ilya; Kurasov, Pavel; Galkin, Daniil (Journal of Applied Engineering Science, 2024)
This paper is devoted to the experimental comparison of accuracy of an operator’s perception of geometrical object sizes and shapes between the different conditions of information perception in the virtual environments and from the electronic displays. The experiments were conducted using a psychophysiological test for the accuracy of perceiving geometrical object sizes and shapes by an operator in the virtual environments and in the conditions of information perception from an electronic display. As a common metric of the accuracy of perceiving geometrical object sizes and shapes, an operator was offered to visually determine the object center of gravity. No significant differences in the measurement results of both the accuracy of perceiving geometrical object sizes and shapes and speed of this process were found based on the different methods of displaying the visual information to an operator.